Anti-interleukin 4 receptor α antibody for the treatment of Chinese bullous pemphigoid patients with diverse comorbidities and a 1-year follow-up: a monocentric real-world study - Wang, Si-Hang; Shan, Ying; Li, Si-Zhe; Zuo, Ya-Gang (Frontiers in Immunology, 2023)
Background Bullous pemphigoid (BP) is a common subepidermal bullous disorder that lacks adequate treatment alternatives. Dupilumab, an anti-interleukin (IL) 4 receptor α antibody blocking Th2 molecules IL-4 and 13, has been used off-label and shown to be effective in refractory BP cases. Methods BP patients with various disease severities and comorbidities were included in this case series. All patients received dupilumab alone or in combination with immunosuppressants in a real-world setting. Complete remission (CR) was defined as the absence of pruritus symptoms and previous BP eruptions, with only hyperpigmentation patches and without newly occurring lesions for at least 4 weeks. Disease relapse was classified as the appearance of three or more new lesions within 1 month or at least one large urticarial or eczematous lesion that did not resolve within a week. Findings Ten individuals were enrolled in this case series. Pruritus symptoms and BP eruptions improved significantly in nine patients (90%). Seven patients (70%) attained CR, including all mild-to-moderate (100%) cases and three of six (50%) severe BP cases. At the dupilumab monotherapy stage, eosinophilia was observed in two severe cases. One patient out of seven (14.3%) relapsed after 1 year of follow-up after CR. Conclusion Treatment of BP with diverse comorbidities with anti-IL-4 receptor α antibody provides further credentials to a prospective randomized study. More impressive efficacy and safety profiles were observed in patients with mild-to-moderate disease after 1 year of follow-up. Eosinophilia may occur in patients receiving dupilumab monotherapy.